2020
DOI: 10.7555/jbr.33.20180047
|View full text |Cite
|
Sign up to set email alerts
|

Severer nodular lesion in white matter than in gray matter in simian immunodeficiency virus-infected monkey, but not closely correlated with viral infection

Abstract: Immune cell accumulation and white matter anomaly are common features of HIV (human immunodeficiency virus) -infected patients in combination antiretroviral therapy (cART) era. Neuroimaging tests on cART treated patients displayed prominent diffuse white matter lesions. Notably, immune cell nodular lesion (NL) was a conspicuous type of pathological change in HIV/SIV (simian immunodeficiency virus) infected brain before cART. Therefore, we used SIV infected brain to investigate the distribution of those NLs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Apart from higher number of PC in the WM, we also observed nodular lesions formed by microglia nodules (MN) that were more prevalent in the WM than in the GM of the SIV-infected brain (Zhang et al, 2019), suggesting involvement of microglia in virus-induced WM injury as reported by many other studies (Borrajo et al, 2021;Wallet et al, 2019). The formation of MN in normal appearing WM was also observed in early stage of MS, which occurred before T-cell infiltration (Singh et al, 2013).…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Apart from higher number of PC in the WM, we also observed nodular lesions formed by microglia nodules (MN) that were more prevalent in the WM than in the GM of the SIV-infected brain (Zhang et al, 2019), suggesting involvement of microglia in virus-induced WM injury as reported by many other studies (Borrajo et al, 2021;Wallet et al, 2019). The formation of MN in normal appearing WM was also observed in early stage of MS, which occurred before T-cell infiltration (Singh et al, 2013).…”
Section: Introductionsupporting
confidence: 80%
“…In our recent study, we also observed that the number of MNs was significantly higher in the WM than in the GM in SIV-infected brains (Zhang et al, 2019). Surprisingly, no infected cells were found in a numerous MNs, inferring microglial aggregation was not directly associated with viral infection.…”
mentioning
confidence: 69%
See 3 more Smart Citations